2010
DOI: 10.1007/s12594-010-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Presence of radon in groundwater in parts of Bangalore

Abstract: Presence of high levels of Radon ( 222 Rn) gas was reported from groundwater in Bangalore. To ascertain the ground reality and the nature of the hazards, if any, a study was conducted by the Central Ground Water Board, Bangalore in and around Bangalore city. Groundwater samples from borewells and a dug well were collected and analysed. Available data on Radon gas from both groundwater and surface water sources were also compared. The presence of Radon gas and its concentration in groundwater were examined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…However, the higher concentration may be due to the higher activity concentrations of 226 Ra and higher concentrations of radon in water in all monitored locations. Shiva Prasad et al (9) and Hunse et al (10) have reported the activity concentrations of 226 ) concentrations for the environment of Bangalore were found to be comparable with the observation made elsewhere in India (8) . In general, radon concentrations were found to be higher in mud houses compared with cemented houses (21) .…”
Section: Inhalation Dose Estimatessupporting
confidence: 63%
See 4 more Smart Citations
“…However, the higher concentration may be due to the higher activity concentrations of 226 Ra and higher concentrations of radon in water in all monitored locations. Shiva Prasad et al (9) and Hunse et al (10) have reported the activity concentrations of 226 ) concentrations for the environment of Bangalore were found to be comparable with the observation made elsewhere in India (8) . In general, radon concentrations were found to be higher in mud houses compared with cemented houses (21) .…”
Section: Inhalation Dose Estimatessupporting
confidence: 63%
“…Some buildings with higher radon levels were found on gravel, but all the lower values were observed in Rajajinagar area. This may be due to the lower activity concentrations (9) of 226 Ra and lower radon concentration in ground water in surrounding area (10) . However, the higher concentration may be due to the higher activity concentrations of 226 Ra and higher concentrations of radon in water in all monitored locations.…”
Section: Inhalation Dose Estimatesmentioning
confidence: 99%
See 3 more Smart Citations